Supercritical Extraction and Compound Profiling of Diverse Edible Mushroom Species - Slađana Krivošija; Nataša Nastić; Milica Karadžić Banjac; Strahinja Kovačević; Sanja Podunavac-Kuzmanović; Senka Vidović (Foods)
Mushrooms are a raw material rich in many nutritional compounds, and that is why a number of them are widely known as functional food. They contain fatty acids, carbohydrates, lycopene, sterols, lovastatin, trace elements, and other valuable compounds that show a wide range of properties, such as hepatoprotective, anticancer, antiviral, etc. For more efficient utilisation of mushrooms’ biologically active substances, widespread supercritical carbon dioxide extraction (Sc-CO2) was used as an efficient way to isolate the high-value phytoconstituents from this type of raw material. Using Sc-CO2, the extracts of five types of edible mushrooms—Lycoperdon saccatum, Pleurotus ostreatus, Craterellus cornucopioides, Russula Cyanoxantha and Cantharellus cibarius—were obtained. During the Sc-CO2 process, the extraction time was reduced to 4 h compared to the prolonged process time applied in the typical traditional techniques (6–24 h). The extraction pressure (30 MPa) and temperature (40 °C) were constant. Fatty acids and the compounds of steroid structures were determined in the obtained extracts using GC–MS and GC–FID methods of analysis. The dominant compounds identified in the lipid extracts were fatty acids (linoleic, oleic, palmitic and stearic) and sterols (ergosterol, 7,22-ergostadienone and 7,22-ergostadienol). For complete insight into the process and to obtain the value of the extracts, chemometric analysis is provided. Principal component analysis (PCA) and hierarchical cluster analysis (HCA), as well as k-means clustering, showed that Craterellus cornucopioides was distinguished based on the extraction yield results.